Anthropometric study of 13/14-year-old handball players - Lancho, J.; Abdesselam, I.; Berral, C.; Poblador, M.; Nogueras, F.; Berral, F. (5th IOC World Congress on Sport Sciences with the Annual Conference of Science and Medicine in Sport 1999, 1999)
A study was made of the body composition, biotype and proportionality of 13/14-year-old members of the Córdoba Provincial Handball Federation. Eighty-five boys were studied (51 aged 13 -junior category- and 34 aged 14 -cadet category). A complete anthropometric study was made following the ISAK protocol.